Intravitreal and Subconjunctival Melphalan for Retinoblastoma in Transgenic Mice. (10th March 2014) - Shah, Nisha V.; Pham, D. G.; Murray, T. G.; Decatur, C.; Hernandez, E.; Shah, Nikesh N.; Cavalcante, M.; Houston, S. K.
Abstract : Purpose . To measure the chemotherapeutic effects of focal melphalan (intravitreal and subconjunctival) on tumor burden, hypoxia, and vasculature in LHBETATAG murine retinoblastoma model. Methods. LHBETATAG transgenic mice were treated with a single 1 mcg intravitreal injection of melphalan, 100 mcg subconjunctival injection, or semiweekly 10 mcg subconjunctival injections for 3 weeks. At 1 or 3 weeks, eyes were enucleated, serially sectioned, and processed with haematoxylin and eosin (H&E) for tumor burden measurements and probed with immunofluorescence to analyze tumor hypoxia and vasculature. Results . Focal melphalan significantly reduced retinal tumor size ( P < 0.02) when given intravitreally or subconjunctivally. Eyes treated with a one-time intravitreal injection of 1 mcg melphalan had significantly smaller tumors at both 1 week ( P = 0.017) and at 3 weeks after injection ( P = 0.005). Intratumoral hypoxia showed a significant decline in hypoxia at 1 week following intravitreal injection and after maximum dosage of subconjunctival melphalan. Total vasculature was not significantly affected following intravitreal administration. Conclusion . Focal delivery of melphalan via intravitreal or subconjunctival injection has a significant effect on reducing tumor burden, hypoxia, and vasculature, in the treatment of murine retinoblastoma tumors.